Potential Molecular Mechanisms of Bisphenol A in Obesity Development: Bisphenol A and obesity - Amiri-Dashatan, Nasrin; Taheri, Zahra; Asadi, Niosha; Jahangiri , Farnaz; Mozafari, Nikoo; Ramandi, Marzieh; Rezaei , Mitra; Nikzamir, Abdolrahim; Jahani Sherafat, Somayeh; Koushki, Mehdi (International Journal of Medical Toxicology and Forensic Medicine, 2023)
Bisphenol A (BPA), an endocrine disruptor, is associated with metabolic disorders. However, several studies have suggested that exposure to BPA can cause obesity. It has recently got more attention from scientists as a risk factor for obesity due to its ability to mimic natural estrogens and bind to their receptors. Nonetheless, the molecular mechanism underpinning the environmental etiology of metabolic disorders has not been not fully clarified. In this regard, BPA exposure directly disrupts endocrine regulation, neuroimmune and signaling pathways, and gut microbes, resulting in obesity. In addition, epidemiological studies have revealed a significant relationship between BPA exposure and the development of obesity, although conflicting results have been reported. Therefore, this review summarized the possible role and molecular mechanisms associated with BPA exposure that may lead to obesity based on in vivo and in vivo studies.